Assessment of the performance of small field of view gamma cameras for sentinel node imaging. Issue 11 (November 2015) - Ng, Aik Hao; Clay, David; Blackshaw, Patricia E.; Bugby, Sarah L.; Morgan, Paul S.; Lees, John E.; Perkins, Alan C.
Abstract : Objective: To develop a method for the assessment of small field of view (SFOV) gamma cameras using a novel phantom designed to simulate the localization of sentinel nodes in the presence of a high-activity injection site. Materials and methods: The phantom consisted of a cube-shaped acrylic glass support frame. Sixteen acrylic glass plates and nine bars were stacked within the frame to allow a variable configuration of the simulated node depth and node-to-injection site separation. Syringes filled with 99m Tc were used to simulate activity at the injection site and node. Scintigraphic imaging was carried out and the images were assessed subjectively and quantitatively through calculation of the contrast-to-noise ratio. The detection performance of an SFOV gamma camera was then compared with that of a large field of view gamma camera. Results: The detectability studies showed that the SFOV gamma camera could detect low activity in nodes by visual examination of images and with contrast-to-noise ratios ranging from 3 to 62. In particular, the phantom showed the limits of node detection using an SFOV gamma camera over activity ratios less than 1 : 100 and at depths below 45 mm with 25 mm of node-to-injection site separation. Visual subjective assessment of images acquired under the same conditions showed that the SFOV gamma camera was superior to a large field of view camera for the detection of nodes at a node-to-injection site separation of 25 mm. Conclusion: A low-cost phantom has been designed and fabricated that provides a versatile method for the assessment of SFOV gamma cameras intended for sentinel node imaging.